2019
DOI: 10.1103/physrevapplied.12.014015
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Vanadium in 4 H Silicon Carbide for Quantum Technology

Abstract: We study the optical properties of tetravalent vanadium impurities in 4H silicon carbide (4H SiC). Emission from two crystalline sites is observed at wavelengths of 1.28 µm and 1.33 µm, with optical lifetimes of 163 ns and 43 ns. Group theory and ab initio density functional supercell calculations enable unequivocal site assignment and shed light on the spectral features of the defects. We conclude with a brief outlook on applications in quantum photonics. arXiv:1901.05371v2 [quant-ph]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 71 publications
3
85
0
1
Order By: Relevance
“…First optical studies showed strong and sharp luminescence lines, as well as narrow EPR features [46]. The defect was further found to have multiple charge states, which are of interest for spin-to charge conversion [47]. The negative charge state V (−) (also known as is V 3+ ) in for polytypes 4H and 6H, is studied in [45].…”
Section: Quantum Properties Of Silicon Carbide Color Centers (Ab Initmentioning
confidence: 98%
See 3 more Smart Citations
“…First optical studies showed strong and sharp luminescence lines, as well as narrow EPR features [46]. The defect was further found to have multiple charge states, which are of interest for spin-to charge conversion [47]. The negative charge state V (−) (also known as is V 3+ ) in for polytypes 4H and 6H, is studied in [45].…”
Section: Quantum Properties Of Silicon Carbide Color Centers (Ab Initmentioning
confidence: 98%
“…Among these the V Si [40] V C V Si , [41,42] the N C V Si [43,44] in various polytypes. In addition, some transition metal color centers such as Ti [45], V [45][46][47], and Mo [48]. On the right in red, color centers in SiC observed as single-photon sources with the maximum brightness observed in cts s −1 , among this the CAV [49,50], Si C [22], oxidation [22] and annealing [51] related and unknown, 3C IR emitters [52].…”
Section: Quantum Properties Of Silicon Carbide Color Centers (Ab Initmentioning
confidence: 98%
See 2 more Smart Citations
“…Подобные процессы идут и в случае компенсации доноров азота: если концентрация ванадия выше, чем концентрация некомпенсированного азота, тогда электроны с донорных уровней азота заполняют акцепторные уровни ванадия. В недавней работе [9] были изучены оптические характеристики ванадия в карбиде кремния с целью его применения в квантовой обработке информации и связи. Эти дефекты имеют узкие линии оптического излучения в телекоммуникационном окне (около 1300 нм).…”
Section: Introductionunclassified